Evaluation of watershed development programmes in India using economic surplus method - Kuppannan, Palanisami; Kumar, D.S.; Wani, S.P.; Giordano, Mark (2009)
Watershed programmes in India are contributing to water resources development, agricultural production and ecological balance. Conventional methods to value them using financial measures attempt to quantify the impacts of watershed development in an isolated manner. In order to evaluate the impacts of watershed programmes in a holistic manner, the Economic Surplus (ES) approach has been applied using the data from a cluster of 10 watersheds in the Coimbatore district of Tamil Nadu.The distributional effects of watershed programmes are also captured through the ES method. Hence, possibilities of using this methodology in the future watershed evaluation programmes could be examined. The study has suggested that people's participation, involvement of Panchayati Raj Institutions, local user groups and NGOs alongside institutional support from different levels, viz. the central and state government, district and block levels should be ensured to make the programme more participatory, interactive and cost effective.